EVALUASI PELAKSANAAN PROGRAM BERAS MISKIN (RASKIN) DI KECAMATAN SAMBUTAN KOTA SAMARINDA - Aji Ratna Kusuma (Jurnal Paradigma (JP), 2017)
This research aims to find out to what extent the program of subsidized rice for the needs of Sambutan Sub-district Samarinda has been successful. It is measured by effectiveness, efficiency, sufficiency, distribution, responsiveness, and accuracy and based on those criteria the reccomendations for future policy can be formulated.